Artificial Intelligence as a Population Surveillance Tool: The Case of China - Glišin, Vanja N.; Milašinović, Srđan M.; Lečić, Boriša N. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The development of artificial intelligence (AI) has brought transformative changes to multiple segments of state and society, establishing new trends in governance and adaptation to global processes in the emerging digital era. AI-based systems are widely applied for surveillance purposes and are increasingly present across the world—from video monitoring, biometric scanning, and facial recognition to algorithmic data processing and predictive analytics, which inform decisions made by security institutions. For years, China has emphasized the integration of AI into various systems through its strategic documents, including surveillance networks, in which it has emerged as a global leader. China thus represents a paradigmatic case for analyzing the use of AI as a tool for population surveillance, as it actively develops and deploys some of the most advanced monitoring systems—a process that became especially visible during the COVID-19 pandemic. Examining this issue from the perspective of the social sciences and humanities is methodologically justified, as the application of AI in population surveillance extends beyond technical and technological aspects to encompass political, security, sociological, and other implications. Through a qualitative analysis of available literature and official documents on AI development, this paper first identifies and defines the key concepts and, in its second part, applies methods of analysis, synthesis, and contextual examination to address the central research question through the case of China.